Yeasts Isolated from Traditional Brem Bali Show Stress Tolerance Phenotype against Fermentation-Related Stresses - Lenka, Audria Bayu; Astuti, Rika Indri; Listiyowati, Sri (UI Scholars Hub, 2021)
The search for microbes, primarily yeasts with unique characters such as the tolerance against fermentation-related-stresses, is gaining significant interest nowadays. Traditionally made alcoholic beverages can be used as sources for such yeasts, given that during fermentation and storage, microbes may develop stress tolerance responses leading to naturally stress-tolerant yeast strains. In this study, we used an alcoholic beverage, that is, Brem Bali, as the source of potential yeast isolates. We isolated nine yeast isolates from two traditional Brem Bali products. All isolates showed tolerance against high glucose stress (40–50%) and sensitivity against high-temperature stress (37–50 °C). Notably, isolate BT5 showed tolerance phenotype against ethanol stress (up to 12.5%). Notably, the ethanol stress tolerance phenotype shown by isolate BT5 was unlikely correlated to the ability of the isolates in combating other stresses. Based on the internal transcribed spacer sequence, isolates BT2, BT5, and BT6 shared high similarity with Wickerhamomyces anomalus (98%). Further approaches may be needed to clarify the identity of these isolates. Based on our study, isolate BT5 bears potential as a fermentation agent based on its ability to combat high glucose and ethanol stresses.